Public participation of environmental cadre groups in Surabaya city in waste management - Maya Mustika Kartikasari (Cogent Social Sciences, 2024)
This article reveals the role of Surabaya environmental cadre group participation in solving the waste problem in the city of Surabaya. Author want to find out the role of environmental cadres in responding to environmental conditions and city government policies regarding waste and unhealthy environments. The research method is a qualitative approach, by exploring information in depth through observation and in-depth interviews through participant observation with environmental cadre activists. The main focus is on waste and environmental management themes carried out by cadres and their relationship with the city government’s environmental policies. The research findings show that in managing waste and environmental problems, environmental cadres position themselves as articulators of public services. This means that the environmental cadre group ‘carries out/replaces’ the function of the city government in waste management. The cadre group acts as a partner as well as a pressure group for the city government to carry out its public duties. The activities of environmental cadre groups become environmental agents and actors who bridge the relationship between the general public and the city government.